Orações subordinadas adverbiais: as relações de sentido a partir dos pressupostos saussurianos - Veseloski, Carla de Camargo (My University, 2021)
This research analyzes how the Saussurian notion of value can contribute to the teaching of subordinate adverbial clauses as a way of collaborating for the student's understanding of the use of conjunctions in compound periods. For that, it was observed the National Curriculum Parameters and the Common National Curriculum Base on how they guide the teaching of Portuguese language in their documents. It is also analyzed, as the adverbial subordinate clauses are presented in two normative grammars, Bechara and Cunha and Cintra, entitled: Modern Portuguese grammar (2009) and New contemporary Portuguese grammar (2001). Two textbooks were also studied so that it could be observed how they deal with such content, they are: Connects to language (2016) and Portuguese trails and plots (2016). Theoretical contribution is concentrated on the linguist Ferdinand de Saussure, especially on the concepts of language, language, speech, system, linguistic sign, associative and syntagmatic relations and, in particular, the notion of value. In addition to the linguist, other scholars of his theory were revisited, such as Michel Arrivé, Claudine Normand, Löic Depecker, Valdir do Nascimento Flores, Leci Borges, among others. Finally, the content of the textbook which deals with subordinate clauses, what the documents referring to language teaching propose, and how the grammar presents such content, are related to the Saussurian notion of value, which deals with meaning through relation of opposition between the terms in a statement, so that one can work, reflect and propose activities that contemplate the understanding of the statements through this perspective [resumo fornecido pelo autor].
Esta pesquisa analisa como a noção saussuriana de valor pode contribuir para o ensino das orações subordinadas adverbiais como forma de colaborar para a compreensão do estudante em relação ao uso das conjunções nos períodos compostos. Para isso, observou-se os Parâmetros Curriculares Nacionais e a Base Nacional Comum Curricular sobre como norteiam o ensino de língua portuguesa em seus documentos. Também é analisado, como as orações subordinadas adverbiais são apresentadas em duas gramáticas normativas, a de Bechara e Cunha e Cintra, intituladas respectivamente: Moderna gramática Portuguesa (2009) e Nova gramática do português contemporâneo (2001). Dois livros didáticos também foram estudados para que se pudesse observar como eles tratam tal conteúdo, são eles: Se liga na língua (2016) e Português trilhas e tramas (2016). O aporte teórico concentra-se no linguista Ferdinand de Saussure, especialmente nos conceitos de língua, linguagem, fala, sistema, signo linguístico, relações associativas e sintagmáticas e, em especial, a noção valor. Além do linguista outros estudiosos de sua teoria são revisitados, como Michel Arrivé, Claudine Normand, Löic Depecker, Valdir do Nascimento Flores, Leci Borges, entre outros. Por fim, o conteúdo do livro didático que trata das orações subordinadas, o que propõe os documentos referentes ao ensino de língua e como a gramática apresenta tal conteúdo são relacionados com a noção saussuriana de valor, que trata do sentido por meio da relação de oposição entre os termos em um enunciado, para que se possa trabalhar, refletir e propor atividades que contemplem a compreensão dos enunciados por meio dessa perspectiva [resumo fornecido pelo autor].
Keywords: Língua portuguesa - Estudo e ensino; Saussure, Ferdinand de, 1857-1913; Portuguese language - Study and teaching